PENGARUH BOOK-TAX DIFFERENCES TERHADAP PERINGKAT OBLIGASI DI INDONESIA - Christina, Vinna; Abbas, Yulianti; Tjen, Christine (Jurnal Akuntansi dan Keuangan Indonesia, 2010)
This research is aimed to analyze the influence of book-tax differences on bond ratings in Indonesia for six years of observation period (2003-2008) using the ordinal logit regression method. Variables used to proxy book-tax differences are deferred tax expenses and tax-to-book ratios. As apposed to Crabtree and Maher (2009) who found book-tax differences have a negative and significant influence on bond ratings. This research shows that large positive deferred taxes have no significant influence whereas large negative book-tax differences have a positive and significant influence on bond ratings, which means the larger negative book-tax differences from the company will increase the bond rating of that company